2022
DOI: 10.3389/fninf.2022.949926
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for autism spectrum disorder diagnosis using structural magnetic resonance imaging: Promising but challenging

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that affects approximately 1% of the population and causes significant burdens. ASD’s pathogenesis remains elusive; hence, diagnosis is based on a constellation of behaviors. Structural magnetic resonance imaging (sMRI) studies have shown several abnormalities in volumetric and geometric features of the autistic brain. However, inconsistent findings prevented most contributions from being translated into clinical practice. Establishing rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…ML has been effectively applied in the medical field to diagnose neurological disorders, including ASD (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ) and ADHD (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Briguglio et al, 2023 ; Kim et al, 2023 ). These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML has been effectively applied in the medical field to diagnose neurological disorders, including ASD (Vakadkar et al, 2021 ; Bahathiq et al, 2022 ; Briguglio et al, 2023 ) and ADHD (Slobodin et al, 2020 ; Mikolas et al, 2022 ; Briguglio et al, 2023 ; Kim et al, 2023 ). These studies have demonstrated the potential of ML to increase diagnostic accuracy, reduce time to diagnosis and improve reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML) algorithms have demonstrated impressive capabilities in analyzing complex datasets and extracting meaningful patterns in other diseases such as autism spectrum disorder (ASD) or ADHD (Eslami et al, 2021 ; Bahathiq et al, 2022 ; Ehrig et al, 2023 ). By harnessing the power of computational algorithms, researchers can integrate diverse data sources, including physical and cognitive variables, to develop predictive models for FASD diagnosis (Blanck-Lubarsch et al, 2022 ; Ehrig et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ML using brain magnetic resonance imaging scans 19 and brain magnetoencephalography 20 to label ASD cases showed overall lower performance across all metrics. A review of 5 years of ML research using brain imaging to diagnose ASD 21 showed an increasing number of projects. They all suggest the existence of abnormalities, but none could replace clinical assessment.…”
Section: Introductionmentioning
confidence: 99%
“…While other diagnostic tools such as the Autism Diagnostic Observation Schedule, the Childhood Autism Rating Scale, and the Autism Diagnostic Interview-Revised are commonly employed in clinical practice, these methods are more time-consuming. However, these methods are inevitably affected by clinical training, tools, and cultural background, thereby interfering with clinicians’ subjective observations [ 24 , 25 ]. To overcome this limitation, it is not enough to only use the scale results to assist diagnosis.…”
Section: Introductionmentioning
confidence: 99%